Compassionate Canadians : Civic Leaders Discuss Human Rights - Howard-Hassmann, Rhoda E., 1948- (Book collections on Project MUSE., 2003)
Understanding the moral reasoning of these civic leaders helps to illuminate the moral consensus among ordinary Canadian citizens around the formal human rights laws that govern Canada. It also illustrates the sort of human rights policies that Canadians are likely to support.